Thyroid Gland Examination for Thyroid Nodule through Free Hand Fine Needle Aspiration Cytology (FNAC) Versus Ultrasound Guided Core Sampling - Shahid Hussain Mirani, Muhammad Tahir Ali, Dileep Kumar, Khalid Abaidullah, Abdul Rasheed Zai, Muhammad Hanif Memon, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the free hand fine needle aspiration cytology versus ultrasound guided core sampling for thyroid nodule examination in thyroid gland. Study Design: Retrospective study Place and Duration of Study: Department of Surgery Unit-2, Ghulam Muhammad Mahar Medical College Hospital Sukkur from 1st January 2016 to 31st December 2021. Methodology: One hundred patients were divided in two groups. Group A had 50 patients who undergo ultrasonography through Doppler scanning while Group B had equal number of 50 patients which underwent free hand fine needle aspiration cytology. The clinical details were noted and graded as un-satisfactory or lacking follicular cells or else having <6 groups epithelial cells or having sufficient number of follicular cells. Results: The mean age was 31.5±11.8 years and majority of the patients were females 54% in comparison with 46% males. Insufficient cytopathologic cells were noticed in 18% US guided thyroidal nodule examination while similar insufficiency was seen in 44% fine needle aspiration cytology examination. The adequate cytopathological cells were noticed in 82% Ultrasounds while same was only seen in 56% fine needle aspiration cytology. Conclusion: Ultrasound guided core sampling has presented higher adequate cytology cases in comparison to free hand fine needle aspiration cytology cases.